O realismo na representação da favela carioca: uma análise axiográfica de três documentários brasileiros - Sousa, Simplício Neto Ramos de (2006)
Our work consists in an axiographic study of three Brazilian documentaries. These films were made in different moments in history and they propose different styles. Our question is: what axiographic systems are to be found in these three films e how these systems interact with each other? Axiografics is a discipline created by American scholar Bill Nichols. It s an attempt to explore the implantation of values in the configuration of space, in the constitution of a gaze and in the relation of observer to observed. It s an attempt to respond to issues that arouse when it comes to the wider discussion on realistic representation in the western art. Two of those issues are, at first, the conventional aspect of realism, detected by Roland Barthes, who created the concept of effet du reel. At second place, the sensorial aspect of realism, guided by a social voyeurism, detected by Paula Rabinowitz, who created this concept. Our work will deal with filmic facts and historical facts that can be found in three Brazilian documentaries that are good examples of what we should call the favela documentary. These films are examples of a realistic representation of the Brazilian social cultural and economic conditions. And, in cinematic terms they propose different unities of filmic enunciation, of the configuration of space, of camera movements, of editing, of narration, and so on. A brief history of the favela, the typical slum of Rio de Janeiro is part of our analyses. The films are Vida Nova na Favela (1971), made by the Brazilian government, Rocinha 77(1977), directed by Sérgio Péo and Notícias de uma Guerra Partícula (1999)r, directed by João Salles e Kátia Lund.